A Multi-Omics Study on the Effect of Helicobacter Pylori-Related Genes in the Tumor Immunity on Stomach Adenocarcinoma - Wu, Xinrui; Jian, Aiwen; Tang, Haidan; Liu, Wangrui; Liu, Fengyuan; Liu, Shifan; Wu, Huiqun (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Helicobacter pylori (HP), a gram-negative microaerophilic bacterium in spiral shape, colonizes the human stomach with an approximate infection of 50% in the world’s population, which is considered a risk factor for gastritis, peptic ulcers, gastric cancer and other malignancies. HP is also regarded as carcinogenic by inducing mutation and damage of multiple HP-related genes. Stomach adenocarcinoma (STAD) is a common stomach cancer with poor prognosis and high risk of metastasis in advanced stage. Therefore, early diagnosis and targeted therapies are needed for better prognosis. In this study, a scoring system was constructed based on three HP infection-related candidate genes for more accurate prediction of the progression and metastasis of the tumor and response of immunotherapies. Methods: HP infection induced mutation patterns of STAD sample from three cohorts were comprehensively assessed based on 73 HP-related genes, which were then correlated with the immune cell-infiltrating characteristics of the tumor microenvironment (TME). The risk signature was constructed to quantify the influence of HP infection of individual tumors. Subsequently, an accurate Nomogram was generated for improving the clinical applicability of the risk signature. Results: Two distinct HP-related mutation patterns with different immune cell-infiltrating characteristics (ICIC) and survival possibility were identified. It was demonstrated that the evaluation of HP infection-induced mutation patterns of tumor could assist in predicting the stages, phenotypes, stromal activity, genetic diversity and patient prognosis. Low risk score was featured by increased mutation burden and activation of immune responses, with a higher 5-year survival rate and enhanced response to anti-PD-1/L1 immunotherapy. While stromal activation was observed in high-risk score samples, with poorer survival. The efficiency of the risk signature was further testified by the Nomogram. Conclusions: STAD patients with low-risk score demonstrated significant therapeutic advantages and clinical benefits. HP infection-induced mutations play a nonnegligible role in the development of STAD. By quantifying the HP-related mutation patterns of individual tumor will contribute to phenotypes classification, hence guide more effective targeted and personalized therapy and more accurate prediction of metastasis and prognosis.